The Impact on Organizational Structures of Model-based Mechatronic System Design. (2016) - Kellner, A.; Ringhofer, S.; Hehenberger, P.; Weingartner, L.; Friedl, M.
Abstract: For an effective model-based mechatronic system engineering software tools are necessary which support collaboration between the involved disciplines, a single source of information and – among other things – enables integrated workflows. But it is not enough just to rollout a new software tool in the company, in order to use all advantages, also the organizational structure has to be adjusted. This contribution discusses these influences on organizational structures and illustrates an analyzing methodology which can be performed before a rollout in order to give recommendations and hints for necessary changes. The methodology is shown on the industrial example of the rollout of the tool COMOS which is used for the design of sinter plants.